Pretty-printing of trees - Jean G. Vaucher (Software: Practice and Experience, 1980)
A pleasing layout of printed tree structures is difficult to achieve automatically. The paper points out three main problems. First, the horizontal position of a node on the printed page depends on global consideration of the position of other nodes; secondly, the physical characteristics of printers require scanning the tree in left-to-right top-to-bottom sequence; finally, page overflow for wide trees must be handled. These problems are illustrated by analysing the shortcomings of a simple printing algorithm. A suitable general binary tree printing algorithm is presented and its adaptation to other types of trees is shown.